Analisis Hukum Pembelaan Terpaksa Secara Berlebihan Pada Kasus Penembakan Laskar Front Pembela Islam Oleh Anggota Kepolisian - Naufal, Asraf (UMPurwokerto Law Review, 2024)
Abstract This study discusses the elements of the forced defense associated with the shooting of Laskar Front Defenders of Islam by police officers that occurred at KM 50 Cikampek. The purpose of this study is to determine whether the forced defense actions carried out by members of the police are in accordance with the elements of forced defense and whether members of the police are free from criminal responsibility as seen from the Criminal Code Article 49 paragraphs (1) and (2) . Based on this research, it is concluded that the first problem formulation is the elements of forced defense according to the Criminal Code and the second is whether the application of this forced defense case is in accordance with criminal responsibility. This research method is a normative juridical method using the Statue Approach and the Conceptual Approach. keywords: Forced Defense, Shooting, Lascar FPI Abstrak Penelitian ini membahas mengenai unsur-unsur pembelaan terpaksa yang dikatikan oelh kasus penembakan Laskar Front Pembela Islam oleh anggota kepolisian yang terjadi di KM 50 Cikampek. Tujuan penelitian ini adalah untuk menetapkan bawasannya tindakan pembelaan terpaksa yang dilakukan oleh anggota kepolisian apakah sudah sesuai dengan unsur-unsur pembelaan terpaksa dan apakah anggota kepolisian bebas dari pertanggungjawaban pidana dilihat dari Kitab Undang-Undang Hukum Pidana Pasal 49 ayat (1) dan (2). Berdasarkan pada peneltiain ini disimpulkan rumusan masalah yang pertama yaitu unsur-unsur pembelaan terpaksa menurut KUHP dan yang kedua penerapan kasus pembelaan terpaksa ini apakah sudah sesuai dengan pertanggungjawaban pidana. Metode penelitian ini merupakan metode yuridis normatif dengan menggunakan pendekatan Statue Approach dan Conseptual Approach. Kata kunci: Pembelaan Terpaksa, Penembakan, Laskar FPI